2018
DOI: 10.18632/oncotarget.25205
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PIM kinase as a therapeutic strategy in human hepatoblastoma

Abstract: Increasing incidence coupled with poor prognosis and treatments that are virtually unchanged over the past 20 years have made the need for the development of novel therapeutics for hepatoblastoma imperative. PIM kinases have been implicated as drivers of tumorigenesis in multiple cancers, including hepatocellular carcinoma. We hypothesized that PIM kinases, specifically PIM3, would play a role in hepatoblastoma tumorigenesis and that PIM kinase inhibition would affect hepatoblastoma in vitro and in vivo. Param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 40 publications
3
36
0
Order By: Relevance
“…As we have previously shown that PIM kinase inhibition decreases tumorigenicity in hepatoblastoma [22] , we wished to determine whether the selective pan-PIM inhibitor, AZD1208 [26] , may have an effect on the SCLCC phenotype. Treatment of HuH6 and COA67 cells with AZD1208 decreased CD133 expression as measured by Western blotting ( Figure 2 A ) and flow cytometry for CD133 expression in permeabilized cells ( Figure 2 , B and C ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As we have previously shown that PIM kinase inhibition decreases tumorigenicity in hepatoblastoma [22] , we wished to determine whether the selective pan-PIM inhibitor, AZD1208 [26] , may have an effect on the SCLCC phenotype. Treatment of HuH6 and COA67 cells with AZD1208 decreased CD133 expression as measured by Western blotting ( Figure 2 A ) and flow cytometry for CD133 expression in permeabilized cells ( Figure 2 , B and C ).…”
Section: Resultsmentioning
confidence: 99%
“…We examined the phenotypic effects of PIM inhibition on the SCLCC versus non-SCLCC populations to determine whether hepatoblastoma SCLCCs exhibited resistance to PIM kinases. We have previously demonstrated that PIM kinases, specifically PIM3, decreased hepatoblastoma proliferation and motility and induced apoptosis [22] . We showed in the current study that both SCLCCs and non-SCLCCs exhibited decreased proliferation and motility and increased apoptosis with PIM inhibition.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…An additional piece of the surgical specimen was placed in formalin and embedded in paraffin for immunohistochemistry. To establish the COA3 and COA6 PDXs, fresh tissue was kept in Roswell Park Memorial Institute (RPMI) 1640 medium on ice for transport and 27 mm 3 chunks were transplanted in a sterile fashion subcutaneously in the flank of female NOD SCID mice (Envigo, Prattville, AL) under anesthesia with 3% inhalational isoflurane as previously described 26,27 . Mice were maintained in specific pathogen free housing.…”
Section: Discussionmentioning
confidence: 99%